TURKEY’S ENGAGEMENT IN THE CONFLICT OF NAGORNO-KARABAKH - Muhammad Rois Adzkia; Sugeng Riyanto (Jurusan Ilmu Hubungan Internasional, 2021)
The background of the Nagorno-Karabakh conflict is the struggle for the territory between Azerbaijan and Armenia. Because internationally the territory is recognized as belonging to Azerbaijan, the majority of its population is the Armenian diaspora. This issue is considered important because the region is quite strategic internationally and involves many actors. This research was conducted to find out why Turkey was involved in this conflict. Where the results concluded that Turkey has an interest in securing energy supplies, selling weapons, reducing Russia's influence, and strengthening its influence in the international world besides helping Azerbaijan crush the separatist groups in Nagorno-Karabakh who want to escape from Azerbaijan.